2014
DOI: 10.1186/s13058-014-0475-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of BRCA1/2defects with genomic scores predictive of DNA damage repair deficiency among breast cancer subtypes

Abstract: IntroductionHomologous recombination (HR) DNA repair is of clinical relevance in breast cancer. Three DNA-based homologous recombination deficiency (HRD) scores (HRD-loss of heterozygosity score (LOH), HRD-telomeric allelic imbalance score (TAI), and HRD-large-scale state transition score (LST)) have been developed that are highly correlated with defects in BRCA1/2, and are associated with response to platinum therapy in triple negative breast and ovarian cancer. This study examines the frequency of BRCA1/2 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
329
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(348 citation statements)
references
References 16 publications
16
329
1
2
Order By: Relevance
“…These three genome-based scores (telomeric AI, LST and LOH) have been assessed as a combined homologous recombination deficiency (HRD) score (HRD Index) in various cohorts of breast cancer samples. The assay, developed using next generation sequencing, was collectively a more sensitive predictor of BRCA deficiency than individual parameters [92] and identified patients with increased benefit to neoadjuvant platinum based therapy [66,93]. Similar findings have been reported reflecting the burden of allelic imbalanced copy number alterations and response to platinum-based chemotherapy [70].…”
Section: Clinical Utility Of Mutation Signaturessupporting
confidence: 62%
“…These three genome-based scores (telomeric AI, LST and LOH) have been assessed as a combined homologous recombination deficiency (HRD) score (HRD Index) in various cohorts of breast cancer samples. The assay, developed using next generation sequencing, was collectively a more sensitive predictor of BRCA deficiency than individual parameters [92] and identified patients with increased benefit to neoadjuvant platinum based therapy [66,93]. Similar findings have been reported reflecting the burden of allelic imbalanced copy number alterations and response to platinum-based chemotherapy [70].…”
Section: Clinical Utility Of Mutation Signaturessupporting
confidence: 62%
“…The Homologous Recombination Deficiency ('HRD') assay measures levels of genomic instability or 'scarring' caused by any number of alterations in DNA repair capacity. At present, the HRD assay incorporates three measures of genomic instability: telomeric allelic imbalance (TAI; the number of regions with allelic imbalance that extend to the subtelomere, but do not cross the centromere), loss of heterozygosity (LOH; the number of regions > 15 Mb and less than one chromosome lost across the genome), and large-scale state transitions (LST; the number of chromosomal breaks between adjacent genomic regions longer than 10 Mb after filtering regions < 3 Mb) [25][26][27]. The HRD score is currently calculated by adding the LOH, TAI, and LST scores and is a continuous score from 0 to 100 with a score of < 41 (previously < 10) as HR proficient and ≥ 42 (previously ≥ 10) as HR deficient.…”
Section: Genomic Scars and Mutational Signatures As Hr Deficiency Biomentioning
confidence: 99%
“…Recently, multiple groups have reported that the HRD assay can be used to identify both BRCA1/2 mutant and wild-type TNBC patients more likely to achieve a favorable response to platinum-based neoadjuvant chemotherapy [27]. In the neoadjuvant PrECOG 0105 trial, responders to this platinum-based therapy had significantly higher mean HRD-LOH scores compared to non-responders; this was true for both BRCA1/2 wild-type and mutant responders [28].…”
Section: Genomic Scars and Mutational Signatures As Hr Deficiency Biomentioning
confidence: 99%
“…The viral vectors presented here may be used as part of a homologous recombination deficiency test to determine whether a cancer patient would be a good candidate for treatment with PARP inhibitors. Previous and ongoing investigations to develop a laboratory test that detects homologous recombination deficiency use deep sequencing-based genomic analysis of the loss of heterozygosity, as they are caused for example by the mutation of BRCA1/2 genes [42,43]. In contrast, blocking PARP activation using DBD expression followed by low dose exposure to radiation or radiomimetic chemicals inducing DNA strand breaks would identify cells that are hypersensitive compared to appropriate controls as a quick first round screening approach.…”
Section: Discussionmentioning
confidence: 99%